2004
DOI: 10.1007/s00040-003-0722-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of colony distribution in monodomous and polydomous species of North African desert ants, genus Cataglyphis

Abstract: Summary. Two monogynous species of North African desert ants belonging to the formicine genus Cataglyphis exhibit extremely different habitat preferences, population densities, and population structures. C. fortis is the only Cataglyphis species within the salt-pan flats of the Algerian and Tunisian chotts and sebkhas, whereas C. bicolor, alongside C. albicans and C. ruber, inhabits the nutritionally richer low-shrub semi-deserts surrounding the salt pans. We present a comparative study of the spatio-temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…To address these questions, we had to select colonies of both species that were located in the same type of habitat, in our case in bare desert environments devoid of any reliable landmark cues. This was easy for C. fortis, because such featureless terrains define the typical habitat of this species (Dillier and Wehner, 2004), but it was difficult for M. bagoti, a species normally inhabiting densely cluttered desert habitats, which are rich in grass tussocks and loosely scattered trees (Muser et al, 2005;Cheng et al, 2009), i.e. rich in visual cues that have previously been shown to be used as navigational aids (Kohler and Wehner, 2005;Narendra 2007b;Narendra et al, 2007b;Sommer et al, 2008;Graham and Cheng, 2009a;Graham and Cheng, 2009b;Wystrach et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these questions, we had to select colonies of both species that were located in the same type of habitat, in our case in bare desert environments devoid of any reliable landmark cues. This was easy for C. fortis, because such featureless terrains define the typical habitat of this species (Dillier and Wehner, 2004), but it was difficult for M. bagoti, a species normally inhabiting densely cluttered desert habitats, which are rich in grass tussocks and loosely scattered trees (Muser et al, 2005;Cheng et al, 2009), i.e. rich in visual cues that have previously been shown to be used as navigational aids (Kohler and Wehner, 2005;Narendra 2007b;Narendra et al, 2007b;Sommer et al, 2008;Graham and Cheng, 2009a;Graham and Cheng, 2009b;Wystrach et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The question of course remains whether these differences are species specific or environment dependent. In trying to tackle this question, we selected colonies that in both species were located on bare, flat desert ground devoid of any vegetation, stones or pebble, and had been at these locations for at least 3years [for C. fortis (Dillier and Wehner, 2004), for M. bagoti (C.B., K.C. and R.W., personal observations)].…”
Section: Discussionmentioning
confidence: 99%
“…All ants belonged to the same colony, which had not changed its nest location over at least 5 years (Dillier and Wehner, 2004). (Forel 1902, Wehner 1983 were trained to feeders south of their nest (Fig.·1A).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to their congeneric relatives, C. fortis ants occupy a featureless habitat devoid of shrubs or other prominent visual landmarks (Dillier and Wehner, 2004). Even though they are confronted with only a few obvious visual landmarks in their natural environment, and therefore rely predominantly on vector navigation (for a review, see Cheng et al, 2014), many studies have shown their ability to learn and use artificial landmarks successfully (for a review, see Wehner, 2008).…”
Section: Introductionmentioning
confidence: 99%